Night work and incidence of Parkinson's disease in the Danish Nurse Cohort. (15th December 2020) - Jørgensen, Jeanette Therming; Schernhammer, Eva; Papantoniou, Kyriaki; Hansen, Johnni; Westendorp, Rudi G J; Stayner, Leslie; Simonsen, Mette Kildevæld; Andersen, Zorana Jovanovic
Abstract : Objectives: Evidence on the association between night work and Parkinson's disease (PD) is sparse and conflicting, calling for more definitive studies. Methods: We included 20 138 female nurses from the Danish Nurse Cohort without PD who at baseline in 1993 and/or 1999 reported their most common current work schedule (day, evening, night, and rotating (a combination of at least two of these)), including information on lifetime cumulative duration (years) of each shift in a 2009 follow-up survey. We obtained information on PD hospital contacts and PD medication until November 2018 via linkage to the Danish National Patient (inpatient from 1977 and outpatient contacts from 1995 onwards) and Prescription Registers starting in 1995. We defined the incidence of PD as the first-ever hospital contact due to PD, or the first-ever redeemed levodopa prescription, whichever came first. We used Cox regression models to calculate HRs and 95% CIs, adjusting for age, smoking status, coffee consumption and use of hormone replacement therapy. Results: We found no significant difference in PD risk among nurses who reported working evening (HR=0.86; 95% CI=0.55 to 1.34), night (HR=1.26; 95% CI=0.79 to 2.02) or rotating shifts (HR=0.83; 95% CI=0.56 to 1.21) at cohort baseline in 1993 or 1999, when compared with permanent day workers. Similarly, persistency of shift work (working the same work schedule for 6+ years) or duration of shift work was not associated with PD risk. Conclusions: Overall, there was little evidence for an association between various shift work schedules including night work and PD in this cohort of middle-aged female nurses.